CNS Aspergillosis - Asif, Dewan Shamsul; Akther, Sumiya; Salam, Safwat Binte; Rahman Siddiqui, Md Mahmudur; Chowdhury, Tasnim Haque (Anwer Khan Modern Medical College Journal, 2022)
Cerebral aspergillosis has the tendency to occur in immune-compromised patients. Less commonly, immune-competent individuals can be affected, with neuroimaging findings being difficult to interpret. A surgical excision with aggressive antifungal therapy is required for a proper management. This case report describes an immune-competent patient with cerebral aspergillosis that presented radiologically as a suspicious mass to be diagnosed pathologically and excised surgically. AKMMC J 2021; 12(2): 107-112